Analysis of Difficulty in Cognitive Learning Outcomes of Grade X Students on Newton’s Law at Senior High School 3 Wera - Almumtahanah, Almumtahanah; Sabaryati, Johri (Journal of Computers for Science and Mathematics Learning, 2024)
The difficulties students face in solving the problem can be an indicator of the extent to which they have mastered the material. Therefore, it is necessary to identify the causes of these difficulties and find solutions to address them. This study aims to determine the level of difficulty in the cognitive learning outcomes of 10th-grade students on Newton’s laws at SMAN 3 Wera and to identify the factors causing these difficulties. This research is a descriptive study with a qualitative approach, involving a sample of 30 students from class X1 at Senior High School (SMAN) 3 Wera. The data collection methods used include tests, interviews, and documentation, with data analysis involving data reduction and verification or conclusion drawing. Based on the research results and discussion, it can be concluded that: (1) The highest level of difficulty in the cognitive learning outcomes of 10th-grade students is found in the C6 cognitive domain (Evaluation), with only 20% of students able to answer C6 questions. Conversely, the least difficulty is found in the C1 cognitive domain (Understanding), with a success rate of 64.07% and 35.93% of students unable to answer the questions. In the C2 cognitive domain (Understanding), the success rate is 60.83%, in the C3 domain (Application) it is 63.3%, with 36.7% of students unable to answer the questions. The moderate difficulty levels are found in the C4 domain (Analysis) with a success rate of 51.7%, in the C5 domain (Synthesis) with a success rate of 53.3%, and in the C6 domain (Evaluation) with a success rate of 46.6%. (2) The factors causing the difficulties in the cognitive learning outcomes of 10th-grade students in solving problems on Newton’s laws at SMAN 3 Wera are (a) difficulty in understanding the problems in the questions and (b) lack of carefulness and haste.